Analysis of the Influence of Contemporary Economic Law on Public Policy in Muslim Majority Countries - Zaki, Amin; Oscar, Scherschligt; Kathryn, Morse (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Modern economic law is very dynamic and covers a lot of things about markets, investment, fiscal policy, and international trade. Sharia principles that emphasize fairness, transparency, and prohibition of usury often influence the implementation of economic law in Muslim-majority countries. The main objective of this study is to analyze the impact of modern economic law on public policy in Muslim-majority countries. Specifically, this study aims to identify the principles of modern economic law that are relevant to Muslim-majority countries, evaluate how these principles are incorporated into public policy, and assess the impact of the application of modern economic law on increasing democratic expectations. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with legal and economic experts, public policy observations in several Muslim-majority countries such as Indonesia, Malaysia, and Saudi Arabia. The results of the study show that Muslim-majority countries face various difficulties in integrating sharia values with the principles of modern economic law. This study finds that modern economic law influences public policy in Muslim-majority countries. It is possible to promote inclusive and sustainable economic growth by incorporating Sharia principles into the structure of modern economic law. However, successful implementation depends largely on the government’s ability to balance market rules with religious principles.